1991
DOI: 10.1128/iai.59.5.1605-1613.1991
|View full text |Cite
|
Sign up to set email alerts
|

In vitro inhibition of adhesion of Candida albicans clinical isolates to human buccal epithelial cells by Fuc alpha 1----2Gal beta-bearing complex carbohydrates

Abstract: The role of cell surface glycoconjugates as possible adhesion receptors for Candida albicans yeasts on human buccal epithelial cells was investigated by using a quantitative radiometric assay involving 14C-metabolically labeled microorganisms. Various structurally defined soluble glycopeptides and oligosaccharides were tested at a low concentration (1 mg/ml) for their ability to competitively inhibit yeast adhesion to such exfoliated cells. Comparisons were also made with various molecular species previously p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
2

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(44 citation statements)
references
References 56 publications
1
41
0
2
Order By: Relevance
“…One of the best-studied Candida adhesins is the fucose binding lectin. Brassart and colleagues were able to inhibit C. albicans adhesion with a panel of milk and meconium oligosaccharides (217). Oligosaccharides bearing a terminal Fuc␣1-2Gal-R (O/H antigen), but not internal fucose residues (Le a , Le b , and Le X ), were able to decrease yeast adhesion by 30 to 40%.…”
Section: Candidamentioning
confidence: 99%
See 1 more Smart Citation
“…One of the best-studied Candida adhesins is the fucose binding lectin. Brassart and colleagues were able to inhibit C. albicans adhesion with a panel of milk and meconium oligosaccharides (217). Oligosaccharides bearing a terminal Fuc␣1-2Gal-R (O/H antigen), but not internal fucose residues (Le a , Le b , and Le X ), were able to decrease yeast adhesion by 30 to 40%.…”
Section: Candidamentioning
confidence: 99%
“…Candida can recognize stratherin, hydroxyapatite, and RGDcontaining proteins such as fibronectin and fibrinogen (213). Candida species also possess lectin-like adhesins, with binding to LacCer, asialo-GM1, Le a , and H-active glycans (213)(214)(215)(216)(217)(218)(219). The type of adhesin expressed varies by strain and is influenced by growth conditions (218)(219)(220).…”
Section: Candidamentioning
confidence: 99%
“…Ding et al () indicated that UFH could attenuate inflammation and coagulation and prevent lethality in endotoxemic mice. Several experimental studies have shown important immunomodulatory activity of heparin with modulating platelet activation (Anaissie et al , ), leucocyte recruitment (Eggimann et al , ), lipopolysaccharide (LPS)‐stimulated release of cytokines (Blot et al , ), expression of adhesion molecules (Rex et al , ), and angiogenesis (Brassart et al , ). Heparin modulates pulmonary hypertension, hypoxaemia, neutrophil migration, and oedema formation in endotoxaemic models (Hocking et al , ; Meyer et al , ; Darien et al , ).…”
Section: Immunomodulationmentioning
confidence: 99%
“…Candida have the ability to produce virulence factors that enhance their capacity to colonize mucosal surfaces and to invade host tissues by disrupting host cell membranes. 43 Proteinases and species-specific phospholipases account for most secretory proteins acting as virulence factors in host cell and animal models of candidiasis. 44 Candida also have the ability to switch between different phenotypic forms in response to environmental conditions.…”
Section: Virulence Factorsmentioning
confidence: 99%